Numerical Focusing of a Wide Field-of-View Instrument for Monitoring the Planetary Energy Budget - Anum Barki Ashraf; J. Robert Mahan; Kory J. Priestley; Mohan Shankar (Proceedings, 2019)
Wide field-of-view optical instruments based on Ritchey-Crétien telescopes have been proposed to replace narrow field-of-view scanning instruments for Earth radiation budget monitoring applications. A disadvantage of such instruments is that they are subject to significant focal plane distortion. A novel numerical focusing scheme is proposed and demonstrated using a Monte Carlo ray-trace-based simulation of the performance of a candidate instrument. Results are presented which indicate that image recovery error can be significantly reduced using the proposed algorithm.